Analysis of the effectiveness of ground‐based VLF wave observations for predicting or nowcasting relativistic electron flux at geostationary orbit. Issue 3 (30th March 2015) - Simms, Laura E.; Engebretson, Mark J.; Smith, A. J.; Clilverd, Mark; Pilipenko, Viacheslav; Reeves, Geoffrey D.
Abstract: Poststorm relativistic electron flux enhancement at geosynchronous orbit has shown correlation with very low frequency (VLF) waves measured by satellite in situ. However, our previous study found little correlation between electron flux and VLF measured by a ground‐based instrument at Halley, Antarctica. Here we explore several possible explanations for this low correlation. Using 220 storms (1992–2002), our previous work developed a predictive model of the poststorm flux at geosynchronous orbit based on explanatory variables measured a day or two before the flux increase. In a nowcast model, we use averages of variables from the time period when flux is rising during the recovery phase of geomagnetic storms and limit the VLF (1.0 kHz) measure to the dawn period at Halley (09:00–12:00 UT). This improves the simple correlation of VLF wave intensity with flux, although the VLF effect in an overall multiple regression is still much less than that of other factors. When analyses are performed separately for season and interplanetary magnetic field (IMF) Bz orientation, VLF outweighs the influence of other factors only during winter months when IMF Bz is in an average northward orientation. Key Points: Dawn ground VLF waves correlate with relativistic flux Best ground VLF‐flux correlations in winter during northward IMF Bz conditions VLF‐flux correlation is low compared to other factors